2022
DOI: 10.1128/msphere.00194-22
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas hydrophila Induces Skin Disturbance through Mucosal Microbiota Dysbiosis in Striped Catfish ( Pangasianodon hypophthalmus )

Abstract: The fish skin mucosal microbiota is essential in modulating the host response to the presence of pathogens. Our study provides a platform to study both the correlation and causation of the interactions among the pathogen, fish skin, and the skin mucosal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Aeromonas hydrophila , e.g. is ubiquitous within freshwater environments and is associated with diseases including bacterial haemorrhagic septicaemia and epizootic ulcerative syndrome (Lategan et al 2004 , Chen et al 2022 ). Flavobacterium psychrophilum is the primary agent of bacterial cold-water disease and rainbow trout fry syndrome, which is one of the main sources of economic loss of the salmonid industry (Duchaud et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas hydrophila , e.g. is ubiquitous within freshwater environments and is associated with diseases including bacterial haemorrhagic septicaemia and epizootic ulcerative syndrome (Lategan et al 2004 , Chen et al 2022 ). Flavobacterium psychrophilum is the primary agent of bacterial cold-water disease and rainbow trout fry syndrome, which is one of the main sources of economic loss of the salmonid industry (Duchaud et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, opportunistic pathogens proliferate when the host is under stress ( 44 ). A significant increase in opportunistic bacteria has been reported in the skin of diseased fish ( 45 , 46 ). Proliferation of Klebsiella in the feces of infected fish may also be associated with stress in ayu as indicated by the increase in cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…on the skin samples (Reid et al 2017). A recent study on striped catfish (Pangasianodon hypophthalmus) challenged with Aeromonas hydrophila similarly showed that pathogen concentration stimulates the skin immune response by altering the mucosal microbiota and increasing the prevalence of opportunistic pathogens (Chen et al 2022). Li et al (2017b) reported that during "red-operculum" disease in crucian carp (Carassius auratus), genera belonging to Aeromonas, Vibrio, and Shewanella were dominant while in healthy fish genera from Cetobacterium, Cyanobacterium and Clostridiaceae were more abundant.…”
Section: Diseases/infectionsmentioning
confidence: 99%